Pemaknaan Murtad Perspektif K.H. Sholeh Darat: Telaah Terhadap Kitab Majmu’at Al-Syariat Al-Kafiyat Li Al-Awam - muhamad ichrom (Nizham Journal of Islamic Studies, 2022)
The work of the Nusantrara clerics cannot be separated from the background conditions at that time. The 19th century was the final chapter of colonialism in Indonesia, the quality and spirit of the Ulama's struggle became one of the determinants of independence. One of them is K.H. Sholeh Darat, is an Nusantara cleric who has a firm view of deviant understandings of both the issue of faith and something that smells of colonialism. This research is a literature research with hermeneutics as the data analysis. The primary source in this study is a book by K.H. Sholeh Darat entitled Majmu'at al Syariat al-Kafiyat Li Al-Awam. This paper is equipped with the hermeneutic method of the book. The author intends to see the background of the opinion on the concept of apostasy when it was drawn in the situation of the Indonesian nation. Indonesia at that time facing colonialism at that time. In the Book of Majmu'at al Syariat al-Kafiyat Li Al-Awam K.H. Sholeh wrote that apostasy has three categories: apostasy by itiqod (belief) and second, apostasy by speech and thirdly apostasy by action. Such a view certainly does not come from a vacuum time, but because of the background and situation that demands it. It can be concluded that the thinking style of KH. Muhammad Sholeh al-Samarani is responsive, simple, upholds cultural values, nationalism, and locality, and tends to be Sufistic